Технології реінжинірингу баз даних - Горішня, К. О. (Харківський національний університет радіоелектроніки, 2024)
In today's information society, where data is a key resource, effective database management becomes a critical task for enterprises. The database structure is one of the main factors affecting the speed of query processing. Database reengineering is the process of modifying and rebuilding existing databases in order to improve their efficiency, productivity and ensure compliance with user needs. That is why the analysis and improvement of existing methods is relevant today. This paper considers three methods of database reengineering: business process modeling; analysis of user requirements; the method of materialized representations. An analysis of three main methods has been carried out, which allows us to conclude about the feasibility of using the method of materialized representations.
Keywords: реінжиніринг; технології реінжинірингу; бази даних; програмні системи; обробка даних; ER-діаграми